The Value of Next-Generation Sequencing in the Screening and Evaluation of Hematologic Neoplasms in Clinical Practice. Issue 5 (26th December 2019) - Northrup, Victoria; Maybank, Allison; Carson, Nancy; Rahmeh, Tarek
Abstract: Objectives: The implementation of next-generation sequencing (NGS) in routine clinical hematology practice remains limited. We evaluate the clinical value of NGS in the screening, diagnosis, and follow-up in hematologic neoplasms. Methods: A targeted NGS panel was used to assess a total of 178 patients for questionable or previously diagnosed myeloid neoplasms. Results: Gene variants were identified in 53% of patients. Novel variants were identified in 29% of patients and variants of unknown significance in 34%. Bone marrow samples yielded a higher number of variants than in peripheral blood. NGS is a more sensitive test than conventional cytogenetics. In several cases, NGS played a key role in the screening, diagnostics, prognostic stratification, and the clinical follow-up of a wide variety of myeloid neoplasms. Conclusions: NGS is an effective tool in the evaluation of suspected and confirmed hematologic neoplasms and could become part of the routine workup of patients.